La cible d’inflation de la Fed : continuité ou rupture ? - Emmanuel Carré (Revue de la Régulation)
The 25th of January 2012, Chairman Bernanke’s Fed announced a 2% inflation target, although this idea was not accepted under previous Chairman Greenspan. How and why the Fed has changed its preferences? How does the Fed justify its decision? To tackle these questions, the approach of central bank communication is followed. Like Meade (2010), Meade and Thornton (2012), transcripts of the Federal Open Market Committee meetings are examined, as well as its speeches and minutes. The article inspects the origins of the Fed’s inflation target by establishing the history of the debate on the inflation target (and inflation targeting) inside the Fed since 1995. Next are examined the design and theoretical foundations of the inflation target presented in Fed’s communications, especially in the context of current financial crisis. Finally, we analyze the theoretical and empirical limits of the inflation target’s foundations.